Bone Plate Fixation: Its Relationship with Implant Induced Osteoporosis - Field, J. R. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
The use of internal fixation devices for fracture repair induces profound changes in the affected bone. The factors implicated in the development of implant induced osteoporosis have been extensively studied. The processes following bone plate fixation which results in vascular and structural changes to the bone have not been accurately described. There are many inconsistencies in the design of experimental studies and in data interpretation which confound the issue.Implant induced osteoporosis appears to be a biphasic phenomenon following the application of rigid internal fixation, with an early-onset osteonecrosis (8-12 weeks) elicited through cortical vascular insufficiency, followed by osteoporosis (24-36 weeks) induced by stress redistribution.The development of implant induced osteoporosis appears to involve mechanical factors (surgical trauma, screw placement, rigidity of the fixation device), acting in conjunction with vascular insufficiencies related to the bone-plate interface contact area and pressure distribution.Whatever the pathogenesis, the end result is a thinning of the diaphyseal cortices. Should implant removal be deemed necessary such osteoporosis is a cause for concern in view of the bones predisposition to refracture following plate removal. The degree of cortical osteoporosis observed appears to be time-dependent following internal fixaton and as such the clinical outcomes, after implant removal, are also related to the timing of removal.Numerous factors have been implicated in the development of the vascular and structural changes that follow the plating of bone. It appears that implant induced osteoporosis has a multifactorial pathogenesis involving surgical trauma, screw placement and the rigidity of the fixation device. Elements involved in the interface between plate and bone, such as interface contact area and pressure, are also implicated in the pathogenesis.
Keywords: Osteoporosis; internal fixation; stress protection